Effects of etomidate on blood cortisol, insulin, and glucose levels and PONV rates in smokers - Sumer, Cevdet; Erhan, Omer Lutfi; Ozer, Ayse Belin; Yildiz, Fuat (Tubitak Scientific & Technological Research Council Turkey, 2012)
Aim: To observe differences in the effects of etomidate, used for anesthesia induction, on surgery-induced endocrine response and postoperative nausea and vomiting (PONV) among nonsmokers and smokers. Materials and methods: Eighty adult patients with ASA I-II risk status were randomly divided into 2 groups: smokers (Group I, n = 40) and nonsmokers (Group II, n = 40). Patients were then further divided into subgroups according to the drug used for anesthesia induction, either propofol (Group IP and Group IIP) or etomidate (Group IE and Group IIE). Blood cortisol, insulin, glucose, and white blood cell (WBC) levels were measured and PONV scores were recorded. Results: Blood cortisol values were significantly lower in Group IE and Group IIE compared to Group IP and Group HP during the 1st and 2nd hours after induction. By the 8th hour, blood insulin levels had increased significantly compared to the baseline values in Groups IE, IP, and IIP. Blood glucose levels were significantly higher in Group IIE compared to both Group IP and Group IIP. There was no significant difference between the WBC levels of the different groups. PONY scores were significantly higher in Group IIE compared to the other groups. Conclusion: We determined that the use of etomidate causes a lower stress response and more PONV compared to propofol, while smoking increases the stress response and decreases PONV.
Keywords: Anesthesia; smoking; cortisol; etomidate; PONV